A modified quantum-inspired evolutionary algorithm for minimising network coding operations. (6th January 2021) - Qu, Zhijian; Li, Tiantian; Tan, Xiao; Li, Panjing; Liu, Xiaohong
Network coding operations will benefit the multicast network performances in improving both the transmission throughput and the reliability. Meanwhile, the network coding operations can also bring some additional resource consumption and transmission delay into the multicast network. Thus, minimising the network coding operations is worthy of in-depth studying. To address this resource optimisation problem, an adaptive evolution mechanism-based modified quantum-inspired evolutionary algorithm is presented in this paper. Three evaluation operators were defined and added into the algorithm to improve the global optimisation ability. In the modified quantum-inspired evolutionary algorithm, the state of each population was jointly determined by these three operators. In the algorithm evolution process, the evolution parameters of the algorithm can be determined by the state of each population. To illustrate the effectiveness of the modified algorithm, it was applied to resolve the function optimisation and the network coding recourse minimisation problems respectively. The experiment results indicated that our adaptive evolution mechanism based modified quantum-inspired evolutionary algorithm has better performances both in searching global optimal solution and convergence speed.